On Asymptotically f-Statistical Equivalent Sequences - Sukran Konca; Mehmet Kucukaslan (Journal of the Indonesian Mathematical Society, 2018)
By using modulus functions, we have obtained a generalization of statistical convergence of asymptotically equivalent sequences, a new non-matrix convergence method, which is intermediate between the ordinary convergence and the statistical convergence. Further, we have examined some inclusion relations related to this concept.